Roy Mitchell: Prophet in Our Past - Usmiani, Renate (Theatre Research in Canada / Recherches théâtrales au Canada, 1987)
Roy Mitchell, Canadian pioneer of modernism in the theatre, has been largely ignored by Canadian theatre historians and publishers. Creative Theatre (1929), his summa, was republished in 1969 - in the United States. It is the purpose of this article to give an overview of Mitchell’s innovative theoretical ideas (as expressed in his three books and numerous articles); of the early practical work at the Arts and Letters Club and at Hart House Theatre, which led to these ideas; and of the interrelationship between Mitchell’s aesthetics of the theatre and his theosophist beliefs. Roy Mitchell, pionnier du modernisme théâtral, demeure à peu près inconnu aux historiens de théâtre et aux libraires-éditeurs canadiens. Creative Theatre (1929), le summum de Mitchell, a été republié en 1969 - aux Etats-Unis. Cet article décrit brièvement les théories avant-gardistes de Mitchell; ses débuts pratiques à l’Arts and Letters Club et au Hart House Theatre qui aboutirent à ces théories; et les rapports entre son esthétique théâtrale et ses croyances théosophistes.